2017
DOI: 10.1039/c7nr03042h
|View full text |Cite
|
Sign up to set email alerts
|

Clinically approved PEGylated nanoparticles are covered by a protein corona that boosts the uptake by cancer cells

Abstract: Today, liposomes are an advanced technology of drug carriers with a dozen drugs in clinical practice and many more in clinical trials. A bottleneck associated with the clinical translation of liposomes has long been 'opsonization', i.e. the adsorption of plasma proteins at the liposome surface resulting in their rapid clearance from circulation. For decades, the most popular way to avoid opsonization has been grafting polyethylene glycol (PEG) onto the liposome surface. Recent studies have clarified that graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 60 publications
6
55
0
Order By: Relevance
“…However, recently several research groups reported that protein adsorption is not completely prevented for PEGylated nanocarriers. [37][38][39] In fact, in our previous studies, we were able to show that distinct proteins preferably adsorb to stealth nanocarriers. 35 These so called 'stealth' proteins (e.g.…”
Section: Resultsmentioning
confidence: 81%
“…However, recently several research groups reported that protein adsorption is not completely prevented for PEGylated nanocarriers. [37][38][39] In fact, in our previous studies, we were able to show that distinct proteins preferably adsorb to stealth nanocarriers. 35 These so called 'stealth' proteins (e.g.…”
Section: Resultsmentioning
confidence: 81%
“…Apart from P450 induction and anti-PEG IgM, a number of other factors might contribute to the ABC phenomenon, including the protein corona and lipoprotein receptor. Recently, it has been reported that the protein corona (which mainly consists of complement proteins and apolipoproteins with or without immunoglobulins) formed on polymer nanoparticles including PEG-L plays a predominant role in the clearance of the liposomes from the blood (Pozzi et al, 2014;Papi et al, 2017). In addition, it has been demonstrated that serum albumin and apolipoprotein low-densitylipoprotein receptors also have a positive impact on this phenomenon (Bertrand et al, 2017; Kari et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Depending on the NP dimension, pH of the medium, surface chemistry and type of NPs and proteins, proteins can mediate the formation of a corona at the external surface of NPs [16][17][18]. The unique protein coronas of differently modified or differently sized NPs affect all features of NP -biological systems interactions ranging from induced cytotoxicity to the mechanism of infiltration [19][20][21][22][23]. NPs after uptaking by a physiological environment are coated with biomolecules almost spontaneously [24,25].…”
Section: Introductionmentioning
confidence: 99%